Editor’s Comments - Judith A. Holton (Grounded Theory Review: An International Journal, 2005)
One of our goals in this journal is to present the work of novice grounded theorists so it is a pleasure to feature three such papers in this issue. The fact that the three papers come from three distinct disciplines and three different continents is a testament to the broad application and interest in grounded theory. The three papers also illustrate the developmental learning curve of classic grounded theory (GT).